Phrase verse - Groenewald, P S (South African Journal of African Languages, 2011)
Any metrical utterance has constituents founded in language and in metrics. The totality cannot consist metrically of less than a verse and two segments, and linguistically of less than a sentence. The principles governing metrical structure are that of partition and symmetry. The totality is thus divided into segments by (a) a word boundary marked by rhyme (in Afrikaans and English) or the repetition of a word (in Sepedi), or (b) a phrase boundary. Symmetry is realized by rhyme, quantitative/stress rhythm, an arrangement of units of meaning (only where the segments are divided by a phrase boundary), the repetition of (i) the same number of syllables and (ii) the same number of words. The Sepedi verse is a phrase verse, and that means that: (a) the segments are divided by a phrase boundary; (b) equivalence or symmetry is realized by (i) the repetition of a word or a phrase, (ii) an arrangement of units of meaning and (iii) quantitative rhythm. Adapted from the source document. Reprinted by permission of Bureau for Scientific Publications